Lebanon's state of erosion: Divisions over the conflict in Syria sustain a dangerous stalemate - Heiko Wimmen (Stiftung Wissenschaft und Politik (SWP), 2016)
The repercussions of the war in Syria have produced a prolonged political stalemate in neighboring Lebanon. As the major political blocs in the country are aligned with opposing sides in the Syria conflict, fear of spillover has led major actors to avoid controversial decisions and suspend elections. This has left room for minimal consensus around maintaining the security that has helped shield Lebanon from the chaos next door. But it has also caused the progressive erosion of political legitimacy, which threatens to unravel political institutions and lead to the further fragmentation of political forces. As all sides are tied to external patrons who no longer consider the country a priority, domestic compromise is likely to remain out of reach. Germany and its European partners should step into the void, in particular the one left by the withdrawal of Saudi Arabia, and push for parliamentary elections as a first step toward due process. (SWP Comments)
Keywords: 320